2022
DOI: 10.1111/jbi.14389
|View full text |Cite
|
Sign up to set email alerts
|

Understanding climate change impacts on biome and plant distributions in the Andes: Challenges and opportunities

Abstract: Aim: Climate change is expected to impact mountain biodiversity by shifting species ranges and the biomes they shape. The extent and regional variation in these impacts are still poorly understood, particularly in the highly biodiverse Andes. Regional syntheses of climate change impacts on vegetation are pivotal to identify and guide research priorities. Here we review current data, knowledge and uncertainties in past, present and future climate change impacts on vegetation in the Andes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 179 publications
1
19
0
4
Order By: Relevance
“…Other authors have suggested that increasing vegetation activity in montane systems is related with the occurrence of anomalous rain and snow episodes (Otto et al, 2011;Anderson et al, 2021). Despite our lack of long-term instrumental data, measurements of soil temperature indicate an upward temperature trend (even the short series), which is supported by soil measurements since 1970 for the area data from Halloy (2002, and more recently data not published), accurately reflecting global warming trends (Vuille et al, 2018;Tovar et al, 2022). Soil temperature increases are especially indicative of long term warming because deep soil temperature is more stable than surface temperature, and therefore long-term signals can be better distinguished from background variability.…”
Section: Lakessupporting
confidence: 69%
See 1 more Smart Citation
“…Other authors have suggested that increasing vegetation activity in montane systems is related with the occurrence of anomalous rain and snow episodes (Otto et al, 2011;Anderson et al, 2021). Despite our lack of long-term instrumental data, measurements of soil temperature indicate an upward temperature trend (even the short series), which is supported by soil measurements since 1970 for the area data from Halloy (2002, and more recently data not published), accurately reflecting global warming trends (Vuille et al, 2018;Tovar et al, 2022). Soil temperature increases are especially indicative of long term warming because deep soil temperature is more stable than surface temperature, and therefore long-term signals can be better distinguished from background variability.…”
Section: Lakessupporting
confidence: 69%
“…The dry Central High Andean ecosystems (c. 18 to 35 LS; Tovar et al, 2022) present extreme climatic conditions, with life growing at its physiological limits mainly due to low temperature and limiting resources such as water, nutrients, CO2 and O2 (Körner, 1999;Pauli and Halloy, 2019). In these systems, biological diversity and vegetation productivity are mainly concentrated in wetlands, which play a central role in wildlife and water regulation, as well as human occupation and pastoralism history (Izquierdo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, ecological processes such as colonization and germination could play a big factor for promoting or restricting species range shifts [ 53 ]. Habitat in the upper limits of Cinchona distribution has declined in the last two centuries in Ecuador and Colombia due to agricultural expansion.…”
Section: Discussionmentioning
confidence: 99%
“… source period taxon no sp. no of records analysed country Caldas S2a memoirs [ 24 ], map of C. officinalis [ 53 ] and Andean profiles late colonial Cinchona sp. and C. officinalis n.a.…”
Section: Methodsmentioning
confidence: 99%
“…The Andes biodiversity hotspot hosts over 28,000 plant species [ 1 , 2 ] , of which 3,805 are reported to benefit humanity [ 3 ] . Unfortunately, nuclear genomic resources are currently available for only 179 species [ 4 ] .…”
Section: Introductionmentioning
confidence: 99%